The role of a common european framework in the elaboration of national language curricula and syllabuses - Gouveia, Carlos A. M. (Cadernos de Linguagem e Sociedade, 2010)
Following the Systemic Functional Linguistics based theory and methodology of Positive Discourse Analysis, this paper discusses some of the political, cultural and educational propositions motivating the Council of Europe’s document Common European Framework of Reference for Languages. A close reading of the text clearly shows that while attempting to promote a plurilingual approach to the learning of languages in Europe, the document also calls for a change in teaching practices aiming at a transformation in the dynamics of language relations in Europe. Some of the issues focused upon in the paper derive directly from the document’s stated objectives, namely questions of levelling, standardization, democracy and hegemony, on the one hand, and questions of plurality, independence, empowerment and difference, on the other.